Chromogranin A and neurone‐specific enolase variations during the first 3 months of abiraterone therapy predict outcomes in patients with metastatic castration‐resistant prostate cancer. (19th February 2017) - Fan, Liancheng; Wang, Yanqing; Chi, Chenfei; Pan, Jiahua; Xun, Shangguan; Xin, Zhixiang; Hu, Jianian; Zhou, Lixin; Dong, Baijun; Xue, Wei
Abstract : Objective: To determine the prognostic utility of serum chromogranin A (CgA) and neurone‐specific enolase (NSE) variations during the first 3 months of abiraterone acetate (AA) treatment in patients with metastatic castration‐resistant prostate cancer (mCRPC). Patients and Methods: The serum levels of CgA, NSE were measured at baseline and after 3 months of AA treatment in 40 patients with mCRPC. Outcome measures were prostate‐specific antigen progression‐free survival (PSA‐PFS), radiographic PFS (rPFS), and overall survival (OS). Results: CgA levels were not correlated with NSE levels ( P = 0.296). In multivariate analysis the combination of CgA and NSE (≥1 marker positive vs both markers negative) and the combination of CgA and NSE elevation during the first 3 months of AA treatment (≥1 marker positive vs both markers negative) remained significant predictors of OS, rPFS, and PSA‐PFS. Conclusion: We found that CgA and NSE elevation during the first 3 months of AA treatment and elevated baseline CgA and NSE levels were independent prognostic factors for OS, rPFS and PSA‐PFS in patients with mCRPC treated with AA. This suggests that serial CgA and NSE evaluation may help clinicians in distinguishing patients with mCRPC who would obtain the best survival benefit from AA treatment.